Family Therapy New Intervention Programs and Researches - Irtelli, Floriana (IntechOpen, 2019)
This book is a collection of chapters written by a number of scientists from all over the world, who provide their insights not only into family therapy but also into new interesting interventions, programs, and research. The book adopts a perspective that respects the complexity of human beings and their family relationships. It devotes a space to the deepening of both psychological and social aspects: all themes in each section of the book are deeply connected. This book also focuses on some specific and really innovative topics, including the importance of psychosocial and family factors, complementary approaches, and relational aspects.